2000
DOI: 10.1055/s-2000-8223
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies on Azadirachtin: Asymmetric Synthesis of the Tetracyclic Decalin Part of Azadirachtin

Abstract: A synthesis of the tetracyclic decalin part of azadirachtin in the naturally occurring form is described. The key reactions involve the Corey-Bakshi-Shibata (CBS) asymmetric reduction of the ketone, and an intramolecular Diels-Alder (IMDA) reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 8 publications
0
13
0
2
Order By: Relevance
“…Murai's first generation route also employed an IMDA reaction to construct the decalin core in azadirachtin (Scheme ) 80. 81 Early studies indicated the requirement of the R configuration at C1 to control the diastereoselectivity in this process ( 181 → 182 ) and this critical centre was therefore installed through CBS‐reduction82 of ketone 179 83. The necessary triene was then accessed following an eight‐step sequence ( 180 → 181 ) after which the desired cycloaddition proceeded in good yield and selectivity to afford 182 .…”
Section: Synthesis Of Azadirachtin Decalin Fragmentsmentioning
confidence: 99%
“…Murai's first generation route also employed an IMDA reaction to construct the decalin core in azadirachtin (Scheme ) 80. 81 Early studies indicated the requirement of the R configuration at C1 to control the diastereoselectivity in this process ( 181 → 182 ) and this critical centre was therefore installed through CBS‐reduction82 of ketone 179 83. The necessary triene was then accessed following an eight‐step sequence ( 180 → 181 ) after which the desired cycloaddition proceeded in good yield and selectivity to afford 182 .…”
Section: Synthesis Of Azadirachtin Decalin Fragmentsmentioning
confidence: 99%
“…39 The further selenenylation of α-phenylseleno ketones with NPSP under basic conditions produces diselenoacetals (eq 28). 40 Enolates derived from lactones 41 and β-dicarbonyl compounds 42 have been selenenylated with NPSP, while an enol silyl ether was reported to furnish a mixture of the corresponding α-phenylseleno ketone and enone in modest yield when treated with NPSP and trimethylsilyl triflate 43 Other Reactions. The reaction of 5-hexenylstannanes, such as shown in eq 32, with NPSP and a Lewis acid afforded the corresponding cyclized selenides.…”
Section: %mentioning
confidence: 99%
“…Silyloxyfuran 14 was prepared by from furan 24 19 via metal–halogen exchange followed by 1,2–addition to acetone (Scheme 3). Due to the sensitivity of 14 to the acidic conditions used in the alkylation of dessilyloxyfuran 13 , an alternative alkylation strategy was devised.…”
mentioning
confidence: 99%